THE INFLUENCE OF ROA, CURRENT RATIO, AND DER ON THE COMPANY'S SHARE PRICE - Maulana, Firman Maulana; Rochayatun, Sulis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This study was conducted to examine whether Return On Assets, Current Ratio, and Debt-to-Equity Ratio have an influence on the stock price of PT Goto Gojek Tokopedia Tbk. PT Goto Gojek Tokopedia is a joint company formed by Gojek and Tokopedia. This quantitative study utilized secondary data, specifically financial reports of the company every quarter from 2022-2023. The research approach was non-participant, meaning the researchers did not directly involve themselves in the company's activities. The findings of this study indicate that Return On Assets, Current Ratio, and Debt-to-Equity Ratio does not significantly influence the stock price of PT Goto Gojek Tokopedia Tbk.